To express the equation \( a_{100} = 2_1 + (n-1)6 \) in explicit form, we first need to clarify what the terms represent:
- \( a_n \) typically denotes the \( n \)-th term in a sequence.
- From your example, it looks like \( 2_1 \) might represent a constant (often written as \( a_1 \), which is the first term of the sequence).
- Let's replace \( 2_1 \) with \( a_1 = 2 \) for clarity in our calculations, given that the number \( 2 \) seems to derive from the first term.
The equation is then updated as follows:
\[ a_n = a_1 + (n-1)d \]
Given \( a_1 = 2 \) and \( d = 6 \), we can substitute these values into the formula:
\[ a_n = 2 + (n-1)6 \]
Now, simplify the equation:
\[ a_n = 2 + 6(n-1) \] \[ a_n = 2 + 6n - 6 \] \[ a_n = 6n - 4 \]
So, the explicit formula for the sequence is:
\[ a_n = 6n - 4 \]